Neuroimmune regulation in Hirschsprung’s disease associated enterocolitis - Ji, Haosen; Lai, Dengming; Tou, Jinfa (Frontiers in Immunology, 2023)
Neuroimmune pathways are important part of the regulation of inflammatory response. Nerve cells regulate the functions of various immune cells through neurotransmitters, and then participate in the inflammatory immune response. Hirschsprung's disease (HD) is a congenital abnormal development of intestinal neurons, and Hirschsprung-associated enterocolitis (HAEC) is a common complication, which seriously affects the quality of life and even endangers the lives of children. Neuroimmune regulation mediates the occurrence and development of enteritis, which is an important mechanism. However, there is a lack of review on the role of Neuroimmune regulation in enterocolitis associated with Hirschsprung's disease. Therefore, this paper summarizes the characteristics of the interaction between intestinal nerve cells and immune cells, reviews the neuroimmune regulation mechanism of Hirschsprung's disease associated enterocolitis (HAEC), and looks forward to the potential clinical application value.